2014
DOI: 10.1002/jcp.24705
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Sex‐Linked Variations in Osteogenic and Adipogenic Differentiation Potential of Bone Marrow Multipotent Stromal Cells

Abstract: Bone formation and aging are sexually dimorphic. Yet, definition of the intrinsic molecular differences between male and female multipotent mesenchymal stromal cells (MSC) in bone is lacking. This study assessed sex-linked differences in MSC differentiation in 3-, 6-, and 9-month-old C57BL/6J mice. Analysis of tibiae showed that female mice had lower bone volume fraction and higher adipocyte content in the bone marrow compared to age-matched males. While both males and females lost bone mass in early aging, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Sex differences have been shown to impact various facets of bone metabolism ( 25 27 ). Previous studies on the role of the gut microbiota in bone density examined female mice ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sex differences have been shown to impact various facets of bone metabolism ( 25 27 ). Previous studies on the role of the gut microbiota in bone density examined female mice ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…PLIN1, ATGL and MEDA-4[85, 86]) and the effect of genetic deletion of SERT[87], GPER[88] and CD24[89] on adipogenesis in mice is gender dependent. The mechanisms for this difference appears to be complex including differential sensitivity to activation of the adipogenic transcription factor PPARG[90] and to differences in tissue microenvironments. For example, the balance between TIMP4 and MMP3 expression, which differs in males and females[91], is critical for remodeling the microenvironment to permit adipocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell line derived from a 15-year-old female Caucasian osteosarcoma patient (Rousseau, Lamoureux et al 2010). Furthermore, it was demonstrated that these cell lines show significant differences in proliferation patterns (Lauvrak et al, 2013 (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019). Furthermore, it was demonstrated that these cell lines show significant differences in proliferation patterns (Lauvrak et al, 2013 (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019).…”
Section: U2osmentioning
confidence: 99%
“…However, since primary cells are prone to variance caused by the donor patient (comorbidities, sex, age, etc. ), transferability of study results is limited, thus the donor patients' individual characteristics have to be considered (Bragdon et al, 2015;Friedl et al, 2007;Friedman, Long, & Hankenson, 2006;Widholz et al, 2019).…”
Section: U2osmentioning
confidence: 99%